Grafting of n-butyl acrylate with natural rubber latex film by gamma radiation: a reaction mechanism (Daffodil International University Journal of Science and Technology, 2010)
Natural rubber latex (NRL) and n-butyl acrylate (n-BA) were blended and irradiated at various absorbed doses by gamma rays from Co-60 source at room temperature. The stabilizing effect was determined by measuring the pH and viscosity of NRL with n-BA with the storage time of five weeks. The cross-link density, swelling ratio of the radiation vulcanized rubber film were measured. The cross-link density of the n-BA grafted NRL film was found increasing and the swelling ratio of that film decreasing with the increased absorbed dose. The optimum radiation dose for better cross-linking of natural rubber latex blended with five parts per hundred rubber (phr) n-BA was found 15 kGy absorbed dose. Based on the cross-linking properties a probable cross-linking reaction mechanism for the n-BA grafted natural rubber latex film was developed. Keywords: Natural rubber latex, n-butyl acrylate, Irradiation, Swelling ratio, Cross-link, Reaction mechanism. DOI: 10.3329/diujst.v5i1.4386 Daffodil International University Journal of Science and Technology Vol.5(1) 2010 pp.81-88